Spontaneous Grafting of OH-Terminated Molecules on Si−H Surfaces via Si–O–C Covalent Bonding - Dief, Essam; Le Brun, A.; Ciampi, Simone; Darwish, Nadim (2021)
The surface functionalization of oxide-free hydrogen-terminated silicon (Si−H) enables predictably tuning its electronic properties, by incorporating tailored functionality for applications such as photovoltaics, biosensing and molecular electronics devices. Most of the available chemical functionalization approaches require an external radical initiator, such as UV light, heat or chemical reagents. Here, we report forming organic monolayers on Si–H surfaces using molecules comprising terminal alcohol (–OH) groups. Self-assembled monolayer (SAM) formation is spontaneous, requires no external stimuli–and yields Si–O–C covalently bound monolayers. The SAMs were characterized by X-ray photoelectron spectroscopy (XPS) to determine the chemical bonding, by X-ray reflectometry (XRR) to determine the monolayers thicknesses on the surface and by atomic force microscopy (AFM) to probe surface topography and surface roughness. The redox activity and the electrochemical properties of the SAMs were studied using cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS). The availability and the ease of incorporating OH groups in organic molecules, makes this spontaneous grafting as a reliable method to attach molecules to Si surfaces in applications ranging from sensing to molecular electronics where incorporating radical initiator setups is not accessible.